Natural history of non‐neurogenic overactive bladder and urinary incontinence over 5 years in community‐dwelling older men: The concord health and aging in men project. Issue 2 (12th January 2016) - Noguchi, Naomi; Chan, Lewis; Cumming, Robert G.; Blyth, Fiona M.; Handelsman, David J.; Waite, Louise M.; Le Couteur, David G.; Naganathan, Vasi
Abstract : Aims: To describe the natural history of non‐neurogenic overactive bladder (OAB) and urgency incontinence in community‐dwelling older men. Methods: A representative sample of 1, 705 community‐dwelling men aged 70 and older in a defined geographic area of Sydney, Australia, had their urinary symptoms assessed using the International Prostate Symptom Scores (IPSS) and the International Consultation of Incontinence Questionnaire (ICIQ) at baseline, 2‐year follow‐up, and 5‐year follow‐up. Four hundred and eighty‐eight men without neurological diseases or prostate cancer during follow‐up, or history of urological treatment at baseline were included in the analysis. Urgency incontinence was defined as leakage of urine occurring more than weekly in the above‐defined population. OAB was defined as either urgency or urgency incontinence according to 2002 International Continence Society consensus. Results: Of the men with OAB at baseline, 29% received treatment for OAB or benign prostatic enlargement over 5 years. Of the remaining men, 33% had sustained remission at 2‐year and 5‐year follow‐ups without treatment. Of the men with OAB at 2‐year follow‐up, remission rate at 5‐year follow‐up was 53% in men without OAB at baseline and 27% in men with OAB at baseline ( P = 0.23). No statistically significant difference was found in baseline characteristics between men with sustained remission and men with persistent symptoms. Conclusions: One in three older men with non‐neurogenic OAB had sustained remission of symptoms without medical or surgical interventions. No significant predictor of sustained remission was identified. Neurourol. Urodynam. 36:443–448, 2017 . © 2016 Wiley Periodicals, Inc.